Применение нечетких логик для моделирования показателей технической эстетики - Бердичевский, Е. Г. (НТУ "ХПИ", 2016)
Рассмотрена возможность моделировать важнейшие показатели технической эстетики на основе теории нечетких логик. Предлагаемая методика базируется на использовании теории лингвистических переменных и построении функций принадлежности. Методика позволяет учесть этапность дизайн-проектирования путем определения временного инварианта.

The possibility to modeling the most important indicators of an industrial art on the basis of the theory of fuzzy logics is considered. The offered technique is based on use of the theory of linguistic variables and creation of functions of accessory. The technique allows to consider staging of design design by definition of a temporary invariant.
Application of fuzzy logics for modelling of indicators of the industrial art
Keywords: эстетичность; лингвистические переменные; функции принадлежности; методика; дизайн-проектирование; modeling; indicators of an industrial art; fuzzy logics; linguistic variables